The synthesis and properties research of functionalized polyolefins. (1st November 2022) - Ma, Zhanshan; Ji, Minghang; Pang, Wenmin; Si, Guifu; Chen, Min
Abstract : This work demonstrated a tandem ROMP/hydrogenation approach for the preparation of functionalized polyolefins and their properties were investigated. Abstract : As polyolefins are a predominant class of polymers used globally, tandem ring-opening metathesis polymerization (ROMP) and hydrogenation represent a powerful strategy to prepare functionalized polyolefins. In this contribution, we demonstrated this tandem approach to prepare a series of functionalized polyolefins with aromatic groups in the main chain utilizing ROMP of COE with diene/triene monomers. This strategy can tolerate different diene/triene substrates bearing ether, ester, and phenol functional groups. The molecular weight and the incorporation ratio of polar functional groups can be adjusted by the feed ratio of COE and diene/triene monomers. This tandem ROMP/hydrogenation approach offers new possibilities for the design of novel functionalized polyolefins that are difficult to access by conventional techniques. The accessed functionalized polyolefin demonstrated excellent performance, such as surface, degradation, antioxidant and compatibilization properties that were potentially applicable in practice.